General Description of School Administrative Staff Services in High School Education Units in Mempawah Regency, West Kalimantan Province - Chandra, Chandra; Sukmawati, Sukmawati; Wicaksono, Luhur (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This research is an attempt to find out more about school administrative management in the High School Education Unit in Mempawah Regency, West Kalimantan Province. The research method chosen is Descriptive Qualitative and also with Literature Review in the data collection process. In this study, the subjects of the study were school principals, heads of school administrative staff, school administrative staff who had the task of managing administration in schools. School administrative personnel are part of the education human resources besides teachers who play an important role in the education service process. However, attention to the existence of administrative staff is still lacking. Support from school management, especially school principals, in increasing professionalism, administrative services, increasing competency, ratio of personnel, supporting facilities and welfare is urgently needed. Therefore, it is necessary to make efforts to increase the existence of school administrative staff so that they can provide professional, quality and excellent quality educational administration services.